Seizure During Infliximab Infusion in a Child With Crohn's Disease: An Illustration of a Neurologic Adverse Event Associated With Drug Antibodies. Issue 3 (12th August 2021) - Joseph, Shelly; Reed, Anna W; Cuffari, Carmen
Abstract : Antitumor necrosis factor (anti-TNF) therapy has proven efficacy in the induction and maintenance of remission in children with Crohn's disease (CD). With the increased use of these medications, several adverse events have been associated, including the emergence of neurologic side effects. While demyelinating conditions and neuropathy associated with anti-TNF therapy have been reported in adults, seizures have been anecdotally described in case reports. We describe a case of an adolescent boy who experienced an infliximab-associated seizure during an infusion and the potential role that medication antibody levels may have played in this adverse event.